1977
DOI: 10.1093/ajcn/30.4.531
|View full text |Cite
|
Sign up to set email alerts
|

Chromium deficiency, glucose intolerance, and neuropathy reversed by chromium supplementation, in a patient receiving long-term total parenteral nutrition

Abstract: A white female, now age 40 and receiving total parenteral nutrition for more than 5 years, developed unexpected 15% weight loss after 3 1/2 years of regimen, together with peripheral neuropathy confirmed by nerve conduction measurements. An intravenous glucose tolerance test showed that the fractional rate (K) had decreased to 0.89%/min (normal greater than 1.2). There was observed during this glucose infusion a borderline normal insulin response with a fall in plasma free fatty acids and in plasma leucine. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
224
1
7

Year Published

1979
1979
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(241 citation statements)
references
References 14 publications
5
224
1
7
Order By: Relevance
“…One of the compounds drawing some attention is the mineral chromium, which is thought to play a key role in carbohydrate metabolism by potentiating the action of insulin, leading to increased insulin sensitivity in type 2 diabetes and obesity (8). Dietary deficiency in chromium has been shown to be positively associated with the risk of diabetes (9). Consistently, reduced levels of chromium have been documented in diabetic subjects with existing cardiovascular diseases (10,11).…”
Section: Introductionmentioning
confidence: 76%
“…One of the compounds drawing some attention is the mineral chromium, which is thought to play a key role in carbohydrate metabolism by potentiating the action of insulin, leading to increased insulin sensitivity in type 2 diabetes and obesity (8). Dietary deficiency in chromium has been shown to be positively associated with the risk of diabetes (9). Consistently, reduced levels of chromium have been documented in diabetic subjects with existing cardiovascular diseases (10,11).…”
Section: Introductionmentioning
confidence: 76%
“…4 Because acute chromium deficiency can cause reversible insulin resistance and diabetes, chromium is routinely added to total parenteral nutrition solutions. 5,6 In 2005 the US Food and Drug Administration permitted a qualified health claim indicating that the evidence for chromium picolinate supplements in reducing the risk of insulin resistance and, possibly, T2DM is highly uncertain. 7 Data from clinical and observational studies since then have been mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that chromium supplementation increases glucose metabolism in insulin resistant populations (16,38,51). However, when healthy subjects have been examined, it has been shown that chromium has no effect on glucose metabolism (14,70).…”
Section: Discussionmentioning
confidence: 99%
“…A classic case report published in 1977 was one of the first accounts of the necessity of chromium in the diet (38). A woman who had her intestines removed had to rely on intravenous nutrition.…”
Section: Necessity Of Chromiummentioning
confidence: 99%
See 1 more Smart Citation